2011
DOI: 10.1258/jtt.2011.100919
|View full text |Cite
|
Sign up to set email alerts
|

Home telemental health implementation and outcomes using electronic messaging

Abstract: In 2007, the VA Connecticut Healthcare System began a home electronic messaging programme for mental health patients. During the first two years, 76 patients with diagnoses of schizophrenia, post traumatic stress disorder, depression and substance-use disorders received a home messaging device, which was connected via an ordinary telephone line. There were daily questions, which were based on disease management protocols, and included alerts, data and educational components. Patient data were sent to a nurse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…These findings are also consistent with those of a recent pilot study that similarly considered the utility of the same telehealth device among a sample of mostly male veterans with mental illness (Godleski et al, 2012). This prior study demonstrated the feasibility of automated telehealth because participants reported improved ability to manage their mental health condition, a greater understanding of their mental health condition, and overall satisfaction with using the device (Godleski et al, 2012). Effectiveness was evidenced by decreases in hospital admissions and emergency department visits (Godleski et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are also consistent with those of a recent pilot study that similarly considered the utility of the same telehealth device among a sample of mostly male veterans with mental illness (Godleski et al, 2012). This prior study demonstrated the feasibility of automated telehealth because participants reported improved ability to manage their mental health condition, a greater understanding of their mental health condition, and overall satisfaction with using the device (Godleski et al, 2012). Effectiveness was evidenced by decreases in hospital admissions and emergency department visits (Godleski et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…One recent trial demonstrated the potential feasibility and effectiveness of the Health Buddy ® , a telehealth disease management program supported by nurse care management, as evidenced by reductions in the total number of hospitalizations and emergency department visits among a group of veterans with mental health illness at the VA Connecticut Health Care System (Godleski, Cervone, Vogel, & Rooney, 2012). The 76 participants in this study were predominantly male (89%) and most had major depression (71%) or substance use disorder (18%), although a small number had schizophrenia (7%) or posttraumatic stress disorder (PTSD; 4%) (Godleski et al, 2012). …”
mentioning
confidence: 99%
“…Among these were 4 modified versions of the Health Buddy automated home messaging device delivered across diverse mental health settings (Godleski et al, 2012; Kasckow et al, 2011; Pratt et al, 2013; Pratt et al, 2014), 3 separate evaluations of the Information Technology Aided Relapse Prevention Programme in Schizophrenia (ITAREPS) (Komatsu et al, 2013; Spaniel et al, 2012; Spaniel, Vohlidka, Hrdlicka, et al, 2008; Spaniel, Vohlidka, Kozeny, et al, 2008), and a trial of an online platform for self-managing bipolar disorder (Todd et al, 2014). Measures of feasibility and acceptability included frequency of intervention use over time, response rates, study retention, proportion of devices that were returned undamaged, and participant reported usability (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Important clinical outcomes were also reported. For example, the Health Buddy automated home messaging device appeared to decrease hospital admissions and emergency room visits (Godleski et al, 2012; Pratt et al, 2014), while reductions in mental health severity were observed in studies of mobile interventions targeting symptom management in schizophrenia (Ben-Zeev et al, 2014; Granholm et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Estimated cost savings were explicitly reported in three studies (Williams, Assassa et al 2005, Allcock 2009, Allen, Dennison Himmelfarb et al 2014) where other studies reported decreased use of services which would ultimately result in cost savings for the health care system. Examples of this include decreased use of emergency departments (Newcomb 2006, Owens, Eby et al 2012, Murphy, Siebert et al 2013, Roots and MacDonald 2014, reduced hospital admissions (Newcomb 2006, Allcock 2009, Godleski, Cervone et al 2012, Lowery, Hopp et al 2012, Murphy, Siebert et al 2013, Roots and MacDonald 2014, decreased length of stays (Godleski, Cervone et al 2012) and reduced visits to a general practitioner (Newcomb 2006, Allcock 2009, Enguidanos, Gibbs et al 2012, Murfet, Allen et al 2013, Prasad, Dunn et al 2014. Although the majority of studies reporting on use of services found promising results, two studies reported statistically insignificant results related to changes in the use of hospital and general practitioner services (Tung, Kaufmann et al 2012, Sawatzky, Christie et al 2013).…”
Section: Societal Benefitsmentioning
confidence: 99%